NONLOCAL BACTERIAL ELECTRON TRANSFER TO HEMATITE SURFACES - Rosso K.M.; Zachara J.M.; Fredrickson J.K.; Gorby Y.A.; Smith S.C. (My University, 2003)
Mechanisms by which dissimilatory iron-reducing bacteria utilize iron and manganese oxide minerals as terminal electron acceptors for respiration are poorly understood. In the absence of exogenous electron shuttle compounds, extracellular electron transfer is generally thought to occur through the interfacial contact area between mineral surfaces and attached cells. Possible alternative reduction pathways have been proposed based on the discovery of a link between an excreted quinone and dissimilatory reduction. In this study, we utilize a novel experimental approach to demonstrate that Shewanella putrefaciens reduces the surface of crystalline iron oxides at spatial locations that are distinct from points of attachment.
Keywords: hematite